2013
DOI: 10.1007/s00737-013-0354-y
|View full text |Cite
|
Sign up to set email alerts
|

Mother-child bonding at 1 year; associations with symptoms of postnatal depression and bonding in the first few weeks

Abstract: Some mothers experience neutral or negative feelings toward their new infant. This study examined the association between symptoms of postnatal depression and mother-infant bonding and the persistence of these feelings over the first year. Bonding was assessed using the Mother-Infant Bonding Scale (MIBQ), at four times postnatal, "early weeks" (1-4 weeks), 9 weeks, 16 weeks and 1 year, in 50 depressed, Edinburgh Postnatal Depression scale (EPDS) ≥13 at 4 weeks post natal, and 29 non-depressed mothers. A signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
100
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(119 citation statements)
references
References 38 publications
11
100
0
3
Order By: Relevance
“…Promoting good mother-child attachment during pregnancy may influence the level of postpartum depression [4]. Several studies have demonstrated the association between maternal depression and MIBS [22] [23] [24]. Our present study supports that maternal depressive status affects mother-to-infant bonding in Japan.…”
Section: Discussionsupporting
confidence: 83%
“…Promoting good mother-child attachment during pregnancy may influence the level of postpartum depression [4]. Several studies have demonstrated the association between maternal depression and MIBS [22] [23] [24]. Our present study supports that maternal depressive status affects mother-to-infant bonding in Japan.…”
Section: Discussionsupporting
confidence: 83%
“…It can be used as a screening instrument, because of its short duration and user-friendly setup. Such a reliable and validated scale for measuring pre-as well as postnatal bonding, makes it possible to investigate the predictive value of low prenatal bonding scores on postnatal bonding scores and, possibly, on infant attachment [23]. In clinical practice, it can be helpful in detecting mothers with higher risk for developing problems in bonding.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal postnatal depression has a strong negative association with postnatal bonding [19,[20][21][22][23][24]. On the other hand, social and partner support were found to be positively correlated to postnatal bonding [19,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-partum depression (PPD) is defined as a major depressive episode starting within 4 weeks of delivery, and markedly affects 13% of women within the first 3 months of giving birth. With its high prevalence rate, PPD is ranked as the most common medical complication of child-bearing (Sit & Wisner, 2009); and with its extremely adverse effect on maternal-infant bonding and infant development (O'Higgins, Roberts, Glover, & Taylor, 2013;Poobalan et al, 2007;Weikum, Oberlander, Hensch, & Werker, 2012), it is a critical concern.…”
Section: Periods Of Vulnerabilitymentioning
confidence: 99%